Transformasi Digital Dan Efektivitas Belajar: Pengembangan Sistem E-Learning Sebagai Arsitektur Pedagogis Baru Di SMA Muhammadiyah 2 Palangka Raya.: Digital Transformation and Learning Effectiveness: Development of an E-Learning System as a New Pedagogical Architecture at SMA Muhammadiyah 2 Palangka Raya - Miftahurrizqi Miftahurrizqi; Setio Ardy Nuswantoro (Anterior Jurnal, 2026)
The rapid development of information technology has significantly transformed the education sector, particularly in digital-based learning processes. This study aims to develop and implement a web-based e-learning system to support blended learning at SMA Muhammadiyah 2 Palangka Raya. The research employed a Research and Development (R&D) approach using the Waterfall model, consisting of analysis, design, implementation, testing, and evaluation stages. The system was tested by 10 teachers and 60 students as primary users. The results indicate that all system functions operated effectively based on Black Box Testing, with an effectiveness rate of 88.7% (categorized as very effective) and an average student learning improvement of 15.4%. The developed e-learning system is considered user-friendly, efficient, and capable of enhancing both teaching management and learning outcomes in secondary education.